Evaluation of Fresnel Zone in Ubiquiti Wireless Simulation and Implementation Using 802.11ac - Ahmad Tantoni; Mohammad Taufan Asri Zaen (JISA(Jurnal Informatika dan Sains), 2026)
The development of wireless communication technology is increasing along with the need for high-speed internet access, both in urban and rural areas. Point-to-Point (PtP) technology based on the IEEE 802.11ac standard is one of the main solutions for providing long-distance connectivity, particularly in backhaul networks, ISPs, and inter-building communication. However, the network implementation process often relies on link simulations using software such as ISP Design Center or AirLink, which do not always accurately represent field conditions. Wave propagation factors, terrain contours, and obstacles in the Fresnel Zone significantly affect signal quality. The Fresnel Zone is a three-dimensional propagation area that must be at least 60% free of obstacles for optimal transmission. Previous research has shown limitations in studies related to evaluating the accuracy of Fresnel Zone simulations on Ubiquiti 802.11ac devices. Therefore, this research evaluates and compares the parameters of RX Signal Strength, throughput, channel width, and Fresnel Zone clearance between simulation results and direct field testing on a PtP connection. The research results are expected to serve as a technical reference for network practitioners in validating simulation results and providing recommendations for more accurate and efficient PtP connection design. This research also emphasizes the importance of Line of Sight (LOS) and Fresnel Zone optimization in maintaining the stability of outdoor wireless networks based on IEEE 802.11ac